Trajetórias formativas de professores formadores e suas concepções de biologia e de seu ensino: uma análise a partir dos estatutos estruturantes da biologia - Miranda, Monike Hyasmin Gomes (2015)
Biology as knowledge produced by man has been constituted through the ages, permeated by historical and social contexts. The relentless pursuit of man to understand nature, life and the phenomena it involved, led to humanity biological knowledge that transforms and is transformed in time to time. So to understand Biology is necessary to go beyond the concepts, it must consider the ontological aspects, epistemological and historical-social construction of knowledge. Teachers who train teachers who will teach biology had different training paths, enabling different conceptions of science and biology, which are manifested in their teaching practice in different ways of relating to knowledge, forming the new teachers identity. For that, this study aims to identify the formative trajectory of degree course teachers in Biological Sciences at UFG, it investigates its conceptions of Biology and Biology teaching and discuss about the effects on this way of training science/Biology teachers. To understand these conceptions this study basis on the Four structural laws of biology proposed by Nascimento Júnior, ontological, epistemological, conceptual and social historical. It was developed questionnaire with objective and dissertative questions on the teachers constitution line and their conceptions of biology and its teaching process. We note that the formative paths are complex and heterogeneous. It was found that the concepts of man, nature, life and scientific knowledge construction are related to the way teachers consider that the Biology teaching process must be. Keywords: